A COMPARATIVE STUDY ON JOB SATISFACTION BETWEEN TEACHING AND NON-TEACHING STAFF IN PRIVATE EDUCATIONAL INSTITUTIONS OF BILASPUR DIVISION, CHHATTISGARH - Jyotsna, Tanya; Gupta, Umesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Job satisfaction is a multidimensional concept that significantly affects the productivity and retention of educational employees. While previous studies have largely focused on the satisfaction levels of teaching staff alone, this research explores the comparative job satisfaction between teaching and non-teaching employees working in private schools and colleges across the Bilaspur division of Chhattisgarh. The study employs a mixed-methods approach, collecting data from 300 respondents (200 teaching and 100 non-teaching) across 20 institutions. Using statistical tools such as t-tests, ANOVA, and correlation analysis, the study identifies disparities in satisfaction levels related to salary, recognition, work environment, job security, and participation in decision-making. The results reveal that teaching staff are moderately satisfied overall, whereas non-teaching staff exhibit significantly lower satisfaction, especially concerning recognition and growth opportunities. The study concludes with policy recommendations for inclusive human resource practices that address the unique needs of both workforce segments in private education.